Bach2 overexpression represses Th9 cell differentiation by suppressing IRF4 expression in systemic lupus erythematosus. Issue 2 (22nd December 2020) - Sheng, Yujun; Zhang, Jiali; Li, Keke; Wang, Hongyan; Wang, Wenjun; Wen, Leilei; Gao, Jinping; Tang, Xianfa; Tang, Huayang; Huang, He; Cai, Minglong; Yuan, Tao; et al.
Abstract : Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by abnormal activation of T cells and caused by an imbalance in the production and clearance of apoptotic cells. We previously showed that the transcription regulator Bach2 regulated abnormal B‐cell activation in SLE. Here, we investigated whether Bach2 was also involved in Th9 cell differentiation in SLE. We found that the proportion of Th9 cells was enhanced in the peripheral blood mononuclear cells (PBMC) of SLE patients. The PBMC and CD4 + T cells of SLE patients exhibited a decrease of Bach2 expression and an increase of IL‐9 expression. Furthermore, Bach2 overexpression significantly repressed the levels of PU.1, IRF4, IL‐9, and Th9 cells in the CD4 + T cells of SLE patients and healthy volunteers. In addition, Bach2 overexpression inhibited the levels of IL‐9 and Th9 cells, whereas IRF4 upregulation enhanced the levels of IRF4 and IL‐9 and Th9 cells in the CD4 + T cells of SLE patients and healthy volunteers. The effect of IRF4 up‐regulation was abolished by Bach2 overexpression. In summary, our work suggests that Bach2 overexpression represses Th9 cell differentiation by suppressing IRF4 expression in SLE, and thus, Bach2 may be a novel potential target for SLE treatment. Abstract : Bach2 is closely associated with systemic lupus erythematosus (SLE). Peripheral blood mononuclear cells and CD4 + T cells of SLE patients exhibit a decrease of Bach2 expression and an increase in the proportions of Th9 cells. Bach2 overexpression represses Th9 cell differentiation by suppressing IRF4 expression in SLE.